The anal reflex elicited by cough and sniff: validation of a neglected clinical sign. Issue 10 (16th September 2004) - Chan, C L H; Ponsford, S; Swash, M
Abstract : Background: It is unclear whether contraction of the external anal sphincter (EAS) following a voluntary cough is an integral component of the cough response itself, or a reflex response to the abdominal and pelvic floor dynamics induced by the cough. Clinical experience suggests a reflex origin for this response. Objective: To compare motor latencies for intercostal, abdominal, and EAS muscle contraction after transcranial magnetic stimulation with those following voluntary coughing and sniffing. Methods: A needle electrode inserted into the EAS measured responses, which were confirmed by tonic electromyographic recording. Direct motor latencies from the cerebral cortex to the intercostal, rectus abdominis and EAS muscles were obtained using transcranial magnetic stimulation. Sniff and cough induced responses were also recorded in these muscles. Results: The results suggest that EAS responses following a voluntary cough or sniff represent a polysynaptic reflex. Conclusions: As the cough induced anal reflex response is consistent and easily elicited, its use in clinical neurological examination is appropriate.